The political economy of Kosher Wars - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2002)
In this paper we develop a theory of â exteuroœKosher Warsâ exteuro under which Rabbis (certifying authorities) compete to enhance the level of Jewish observation of their congregations. The level of observance can be seen as the Rabbiâ exteuro™s rents. Our rent-seeking model explains the establishment of Kashrut standards, first with European style community control under a single Rabbi, and then under Americaâ exteuro™s voluntary structure with the possibility of competing Rabbis.
Keywords: D71; D72; Z12; 330; dietary restrictions; Kashrut; kosher; religion; rent-seeking; Rent Seeking; Judentum; Theorie; Europa; USA; Ernährungsverhalten